Brand or friend? A study on relational mobility as the mediator between stress and brand identification - Chi, Boon See (2017)
With possessions’ imperative role in society today, it is not surprising that individuals have been accustomed to form bonds with their favorite brand. This identification has been demonstrated possible to replace social identification, which is essential to an individual’s self-concept and self-worth. Review of past researches illustrates the potential of brand identification as a coping resource to overcome stressors. The present study hypothesizes that relational mobility (the potential of an individual to form and break an interpersonal tie) acts as a mediator to the relationship between stress and perceived value of the brand. Furthermore, the study explores different types of brand value that consumers identify with, namely utilitarian benefit, experiential benefit, and symbolic benefit. The study also hypothesizes that consumable brands are able to evoke greater utilitarian benefit while clothing brand evokes greater experiential benefit. Participants were randomly assigned to different stress (high vs low) and brand (consumable vs clothing) conditions before completing questionnaires on perceived brand value and relational mobility. Although the analysis did not support both hypotheses, it provided an insight to how different brands types moderate the mediating effect hypothesized. Results showed a conditional indirect relationship, whereby stressful condition caused individuals to observe greater relational mobility, which in turn elicit greater perceived value of their favorite brand – only when they are looking at consumable brand specifically.